Evolución de un modelo de gobernabilidad empresarial de TI en una empresa líder del sector agroindustrial (2015)
The project is developed as a response to some of the events that the company is going through as a result of all the initiatives focused on the expansion of its palm border, which sought to replace the need to have access to the largest amount of palm fruit, but that meant a high requirement of resources, among them the financial one, generating in this way a situation of narrowness in the cash flow. The foregoing obliges the company to reformulate its strategy, proposing for 2016 to be profitable, competitive and with a sustainable financial equilibrium. It shows the importance of the alignment of IT goals with corporate goals within the materialization of the company's dream. And that is why it is a key factor that the CIO of the company is an important part of the strategic decisions of the same and as the top management is informed of the Business, the internal and external environment and the culture of the organization . In coherence with the alignment of the IT goals and the Corporate goals, an IT Governance process is identified, which will be worked on and some recommendations of good practices are established that will allow the company to achieve the desired level in the process of Establishment and Maintenance of the IT Governance Framework. A plan of the practices that the company decides to adopt is established, leaving the Enablers, Metas and Metrics structured to guarantee that the expected value will be received and that the life cycle is managed. This shows some examples that the company decides to share.